KNOWLEDGE SHARING AMONG SCHOOL LIBRARY PERSONNEL IN NIGERIA: HOW DO DIGITAL AND MEDIA LITERACIES INTERFERE? - Aramide, Kolawole Akinjide (International Journal of Knowledge Content Development & Technology, 2022)
The study investigated the contributions of digital and media literacies to knowledge sharing among school library personnel in Nigeria. The survey research design was adopted for the study while questionnaire was used to collect data from the 190 respondents that constitute the sample size for the study. Findings from the study revealed a high level of digital and media literacy skills possession by the school library personnel surveyed. Producing information, evaluating digital information, and finding digital were major media and digital information literacy skills that significantly contributed to knowledge sharing among the school library personnel. The study recommended that adequate attention should be given to the development of digital and media literacies of school library personnel in Nigeria to ensure effective and efficient knowledge sharing.